Effects of Saccharomyces boulardii on Neonatal Hyperbilirubinemia: A Randomized Controlled Trial - Serce, Ozge; Gursoy, Tugba; Ovali, Fahri; Karatekin, Guner (American Journal of Perinatology, 2015)
Objective Since probiotics modulate intestinal functions and enterohepatic circulation; they might have an effect on neonatal hyperbilirubinemia treatment. The objective of this study was to investigate the efficacy of Saccharomyces boulardii supplementation on hyperbilirubinemia.Study Design A prospective, double-blind, placebo controlled trial was performed on 35 to 42 gestational weeks' neonates. They were randomized either to receive feeding supplementation with S. boulardii 125 mg every 12 hours or placebo during phototherapy. Serum bilirubin levels were measured at 0, 24th, 48th, 72nd, and 96th hour of phototherapy.Results A total of 119 infants (61 in the control group and 58 in the study group) were enrolled. The duration of phototherapy (2 [1–3] vs. 2 [1–3], p: 0.22) was not different between groups. The levels of bilirubin during phototherapy ([24th hour; 14.1 {12.8–15.7} vs. 13.5 {12.4–14.9}, p: 0.085]; [48th hour; 14.1 {12–15.3} vs. 13.4 {12.4–14.5}, p: 0.41]; [72nd hour; 13.9 {12.2–15.6} vs. 13.5 {12.5–14.5}, p: 0.41]; [96th hour; 14.7 {11.4–15.5} vs. 13.4 {10.7–14.1}, p: 0.24]) or the duration of rebound phototherapy (1 [1–1] vs. 1.5 [1–2], p: 0.40) were lower in the study group than in the controls, but none of the values were statistically significant.Conclusion S. boulardii did not influence the clinical course of hyperbilirubinemia significantly.
Keywords: neonatal hyperbilirubinemia; phototherapy; probiotic; Saccharomyces boulardii